Solar photovoltaic surface cooling using hybrid solar chimney-collector with wavy fins - Zhang Genge; Mohd Suffian Misaran@Misran; Zikuan Zhang; Mohd Adzrie Radzali; Mohd Azlan Ismail (Semarak Ilmu Publishing, 2024)
Elevated temperatures, frequently observed in regions characterized by high ambient heat, markedly diminish the operational efficiency and curtail the lifespan of Solar Photovoltaic (PV) panels. Consequently, it is essential to enhance the sustainability and operational performance of solar energy systems through the mitigation of surface temperatures of solar PV panels. The study investigates the impact of the number of fins on the panel's surface temperature and the airflow within the collector-chimney cavity. Computational Fluid Dynamics (CFD) simulations were employed to determine the optimal number of fins for maximum cooling efficiency. The results indicate that increasing the number of fins initially lowers the solar PV surface temperatures, but the improvements diminish due to increased airflow restrictions. The surface temperature reduction enabled by the fins up to 14.1°C at 50.99°C, which can help mitigate solar PV efficiency losses in hot climates. The CFD simulations accurately predicted the thermal-fluid behaviour and cooling capacity of the hybrid system, as validated against experimental data. The study concludes that the incorporation of optimized wavy cooling fins in a hybrid solar chimney-collector system shows strong potential for passively enhancing solar PV panel cooling and efficiency.